Sweet thunder - Doig, Ivan (Riverhead Books, a member of Penguin Group (USA), 2013)
After inheriting a fixer-upper, newlywed Morrie Morgan returns to 1920s Butte, Montana, to fight a rival newspaper and help the miners working for the Anaconda Copper Mining Company.